ANALISIS KORELASI NlLAl NDVl (NORMALlZED DIFFERENCE VEGETATlON INDEX) DENGAN VEGETATlON DENSlTY DI KHDTK UNlVERSITAS LAMBUNG MANGKURAT - Komang Hendra Pangestu; Ahmad Jauhari; Udiansyah Udiansyah (Universitas Lambung Mangkurat, 2023)
The purpose of this study is to anaIyze the correIation between NDVl (NormaIized Difference Vegetation lndex) and Vegetation Density values using a combination of remote sensing, GIS, and field observations. The method in this study uses NDVI transformation, Advanced vegetation lndex (AVl), Bare SoiI lndex (Bl), Vegetation Density (VD), and field observations. In this study, the NDVI analysis was divided into 4 classes, namely tightly, moderate, rare, and very rare. The determination of the sample based on the specified sampling intensity is 0.2%. The resuIts of the NDVl anaIysis that has been carried out produce a value of 0.07 – 0.88 based on the 4 classes. To produce the VD value, Principal Component Analysis (PCA) is performed. The value of VD is 0.004 – 1.140 where the VD value is corrected using data from field observations. The data used is the value of the Base Area for each class. The results of the VD correction with field data resulted in a value of 0 – 0.68, where the highest density of the area was 68%. The results of the correlation of the NDVI value with the VD value obtained the equation y = 0.749875 + 1.14178x with a regression coefficient (R2) of 0.4647, where the two variables influence 46.47%. The regression coefficient value (R2) is 0.4647 with the interval coefficient value (r) 0.681689 indicating that the relationship between the NDVI value and VD is very strong. The positive regression coefficient (+) means that it is directly proportional, so from the NDVI value, it can be seen that the higher the NDVI value, the higher the vegetation density value.Tujuan penelitian ini yaitu dengan menganalisis korelasi nilai NDVl (NormaIized Difference Vegetation lndex) dengan Vegetation Density menggunakan teknik kombinasi antara penginderaan jauh, SIG dan observasi lapangan. Metode dalam penelitian ini menggunakan transformasi NDVI, Advanced vegetation lndex (AVI), Bare SoiI lndex (BI), Vegetation Density (VD), dan observasi lapangan. Dalam penelitian ini analisis NDVI dibagi menjadi 4 keIas yaitu rapat, sedang, jarang, dan sangat jarang. Penentuan sampel berdasarkan intensitas sampling yang ditentukan yaitu 0,2 %. Hasil dari analisis NDVI yang telah dilakukan menghasilkan nilai 0,07 – 0,88 berdasarkan dari 4 kelas tersebut. Untuk menghasilkan nilai VD dilakukan Principal Component Analysis (PCA). Nilai dari VD yaitu 0,004 – 1,140 yang dimana nilai VD dilakukan koreksi data menggunakan data hasil observasi lapangan. Data yang digunakan adalah nilai dari Luas Bidang Dasar pada setiap kelas. Hasil koreksi VD dengan data lapangan menghasilkan nilai 0 – 0,68 yang dimana kerapatan tertinggi dari wilayah tersebut sebesar 68%. Hasil dari korelasi nilai NDVI dengan nilai VD didapatkan hasil persamaan y = 0.749875 + 1.14178x dengan nilai koefisien regresi (R2) sebesar 0,4647 yang dimana kedua variabel tersebut memiliki pengaruh sebesar 46.47%. NiIai koefisien regresi (R2) sebesar 0,4647 dengan nilai interval koefisien nilai (r) sebesar 0,681689 menandakan bahwa hubungan antara niIai NDVI dengan VD sangat kuat. Nilai koesien regresi positif (+) mengartikan berbanding lurus, sehingga dari nilai NDVI dapat dilihat semakin tinggi nilai NDVI artinya semakin tinggi nilai kerapatan vegetasi.